2007 40th Annual Hawaii International Conference on System Sciences (HICSS'07) 2007
DOI: 10.1109/hicss.2007.307
|View full text |Cite
|
Sign up to set email alerts
|

IT outsourcing for E-government: Lessons from IT outsourcing projects initiated by agricultural organizations of the Korean government

Abstract: The main goal of this study is to conduct an empirical investigation of IT outsourcing projects for E-government and provide useful implications for IT mangers in the public sector. A framework is proposed and diverse IT outsourcing success factors are examined using data collected from the public sector. Fifty nine IT outsourcing projects initiated by agricultural organizations of the Korean government for the last 7 years were used for analysis in this study. A survey research was also conducted from IT mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…• IT specialists are more attractive to private sector (Moon et al 2007) • Problems of recruiting and retaining good IT professionals due to the low payment system (Khalfan and Gough 2002).…”
Section: Social Exchange Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…• IT specialists are more attractive to private sector (Moon et al 2007) • Problems of recruiting and retaining good IT professionals due to the low payment system (Khalfan and Gough 2002).…”
Section: Social Exchange Theorymentioning
confidence: 99%
“…• Obliged by legislation to undertake a rigorous and open supplier selection process (Burnes and Anastasiadis 2003) • Free to choose the suppliers (Burnes and Anastasiadis 2003) • Inflexibility bidding process (Moon et al 2007) • Developments and changes continues during the contract period (Burnes and Anastasiadis 2003) Process Management…”
Section: Social Exchange Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Although most of the success factors for ITO were rigorously considered based on principles and findings from previous research, which are frequently referred to [25], there are still some project that is not fully satisfied by the stakeholders or do not meet stated performance objectives [26]. egov4dev.org (2009) reported that egovernment project failed because there is no lesson learned since knowledge about the failure was not captured, transferred or applied.…”
Section: Malaysia E-government It Outsourcingmentioning
confidence: 99%